The Effectiveness Of The Iqraâ€™ Wheel Game To Enhance Studentsâ€™ Arabic Reading Skills At State Islamic Senior High School 1 Malang - Yanwari, Rizki Safitri; Thoyyibah, Anisatu; Raziqi, M. Ainur (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2021)
Learning media appears to be a pivotal need for learning programs used to reach out learning objectives. This study aims to find out the application and effectiveness of the Iqra' wheel game to enhance students' Arabic reading skills. This study uses a quantitative approach with the type of experiment. The subjects used are language students of tenth grade and 2nd MIPA students of tenth grade with a sampleÂ  60 students. Methods used observation, interviews, questionnaires, tests, and documentation. Data analysis techniques used in research is validity test, reliability test, sample t-test and effectiveness test. The research findings showed that is a significant difference between the pre-test and post-test scores. The pre-test score is quite smaller the post-test score of 84.41 < 90.58. The percentage of N-Gain shows 38.23% with a quite effective category. It can be concluded that the iqra wheel game is â€œquite effectiveâ€ in improving Arabic reading skills.